International Perspectives in Values-Based Mental Health Practice Case Studies and Commentaries - Stoyanov, Drozdstoy (Springer Nature, 2021)
This open access book offers essential information on values-based practice (VBP): the clinical skills involved, teamwork and person-centered care, links between values and evidence, and the importance of partnerships in shared decision-making. Different cultures have different values; for example, partnership in decision-making looks very different, from the highly individualized perspective of European and North American cultures to the collective and family-oriented perspectives common in South East Asia. In turn, African cultures offer yet another perspective, one that falls between these two extremes (called batho pele). The book will benefit everyone concerned with the practical challenges of delivering mental health services. Accordingly, all contributions are developed on the basis of case vignettes, and cover a range of situations in which values underlie tensions or uncertainties regarding how to proceed in clinical practice. Examples include the patient's autonomy and best interest, the physician's commitment to establishing high standards of clinical governance, clinical versus community best interest, institutional versus clinical interests, patients insisting on medically unsound but legal treatments etc. Thus far, VBP publications have mainly dealt with clinical scenarios involving individual values (of clinicians and patients). Our objective with this book is to develop a model of VBP that is culturally much broader in scope. As such, it offers a vital resource for mental health stakeholders in an increasingly inter-connected world. It also offers opportunities for cross-learning in values-based practice between cultures with very different clinical care traditions.